Quality of life in lepromatous leprosy patients - Demir, Betul; Ucak, Haydar; Dertlioglu, Selma Bakar; Demir, Sukru; Guler, Kubilay; Cicek, Demet; Halisdemir, Nurhan (Deri Zuhrevi Hastaliklar Dernegi, 2014)
Background and Design: Leprosy is a chronic infectious disease caused by Mycobacterium leprae bacillus affecting the skin and peripheral nervous system. Leprosy can lead to severe deformities depending on the extent of the disease. In this study, we aimed to investigate the quality of life of patients with lepromatous leprosy. Materials and Methods: Thirty-five patients with lepromatous leprosy and 35 healthy controls were included in the study. The patients were evaluated with the Turkish version of the Dermatology Life Quaky Index (DLQI) and the 36-Item Short Form Health Survey (SF-36). The relationship of quality of life with age, gender, marital status, and the grade of the visual impairment was studied and compared with the healthy controls. Results: Total and all the subgroup DLQI scores were higher in the leprosy group than in the control group (p<0.05). The patients with grade 2 visual impairment were more severely affected by the disease with regard to symptoms/feelings and school/work life as compared to the patients with grade 1 visual impairment (p=0.04, p=0.03, respectively). SF-36 physical functioning, physical role functioning, general health perceptions, vitality, social role functioning, and emotional role functioning scores were statistically lower in the patient group than in the control group (p<0.05). Conclusion: We observed that DLQI scores were lower in patients with lepromatous leprosy than in the control group, while increasing impairment in eyes was found to have a negative impact on quality of life. The SF-36 revealed that physical functioning, physical role functioning, general health perceptions, vitality, social role functioning, emotional role functioning, and mental health were negatively influenced in patients with lepromatous leprosy.
Lepromatöz leprali hastalarin yaşam kalitesi
Keywords: Leprosy; Dermatology Life Quality Index; 36-Item Short Form